The Existence of Aswaja in Shaping Students' Religious Moderation Character Through the Concept of Education Sustainable Development (ESD) at Pakisaji Islamic Middle School - Nur Milan; Yuliana Nur Mustaghfiroh (Ma'arif Journal of Education, Madrasah Innovation and Aswaja Studies, 2026)
This study aims to analyze the role of Ahlussunnah wal Jama’ah (Aswaja) values in shaping students’ religious moderation through the concept of Education for Sustainable Development (ESD) at Pakisaji Islamic Junior High School. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and documentation involving Islamic education teachers, the principal, and students. The findings reveal that the internalization of Aswaja values tawasuth (moderation), tasamuh (tolerance), tawazun (balance), and i’tidal (justice) is integrated into learning, social activities, and ESD-based environmental programs. This implementation not only strengthens students’ moderate, tolerant, environmentally conscious, and fair attitudes but also establishes an Islamic and sustainable school culture. Although some students remain influenced by intolerant narratives on social media, the majority demonstrate positive responses, including active participation in social activities, respect for diversity, and sustainable lifestyle habits. Therefore, the integration of Aswaja and ESD significantly contributes to creating a holistic educational ecosystem that nurtures a generation of moderate, tolerant, environmentally aware, and empathetic individuals.